Perancangan Kursi Jahit Ergonomis untuk Memperbaiki Postur Pekerja Pada CV. Gusti Batik dengan Menggunakan Metode Rapid Entire Body Assessment (Reba) dan Time Study - Fingka Dyah Puspitarini; Halimah Anis Kurlillah; Nenzy Agustin Dwi Prahesti; Ahmad Luqmanul Farras; Adelia Tata Anggita; Suseno Suseno (Politeknik Kampar, 2024)
Gusti Batik is a company that operates in the fashion trade sector, especially batik clothing. In carrying out its work, there are several risks that can affect health caused by workplace conditions that are not in accordance with the needs of workers. Therefore, an ergonomic sewing chair was designed to improve the posture of the tailors at the Gusti Batik convection which was carried out by analyzing body posture using the Rapid Entire Body Assessment (REBA), Time Study, and Anthropometry Methods. Improvements were made in order to increase productivity in the sewing process by making ergonomic sewing chairs that Gusti Batik hopes can create a healthier and more productive work environment, reduce the risk of injury, and increase operational efficiency through continuous ergonomic improvements. Based on calculations using the REBA tailor method before the repair, a REBA score of 8 was obtained and after the repair, a REBA score of 5 was obtained. The results of the study using the time study method before the repair obtained a total standard time of 2.7 hours/unit. By setting the standard time to 2.5 hours/unit from the previous 2.7 hours/unit, there was an increase of 0.2 hours/unit.